2010
DOI: 10.1093/toxsci/kfq156
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Interaction of Binary and Ternary Mixtures of Estradiol with Bisphenol A and Bisphenol AF in an In Vitro Estrogen-Mediated Transcriptional Activation Assay (T47D-KBluc)

Abstract: Exposure to xenoestrogens occurs against a backdrop to physiological levels of endogenous estrogens. Endogenous estrogen levels vary from low levels in early childhood to high levels during pregnancy and in young women. However, few studies have addressed how xenoestrogens interact with endogenous estrogens. The current study was designed to characterize the individual dose-response curves of estradiol-17beta (E(2)), bisphenol A (BPA), tetrabromo-bisphenol A (TBBPA), and bisphenol AF (BPAF, 4,4'-hexafluoroisop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 39 publications
(53 reference statements)
1
30
0
Order By: Relevance
“…All of these effects of BPA have been attributed to effects on steroid hormone receptors such as ER (Matsushima et al, 2010). BPA and BPAF have been shown to induce estrogen-dependent response in vitro via binding to ER (Song et al, 2006;Bermudez et al, 2010), whereas studies on the estrogenic activity of TBBPA in vitro are inconsistent. The estrogenic activity of TBBPA was examined by several investigators using various in vitro methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these effects of BPA have been attributed to effects on steroid hormone receptors such as ER (Matsushima et al, 2010). BPA and BPAF have been shown to induce estrogen-dependent response in vitro via binding to ER (Song et al, 2006;Bermudez et al, 2010), whereas studies on the estrogenic activity of TBBPA in vitro are inconsistent. The estrogenic activity of TBBPA was examined by several investigators using various in vitro methods.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphenol A (BPA) is an important industrial chemical which is widely used in the manufacture of polycarbonated plastic, food can linings, chemical papers, and dentistry sealants (Bermudez et al, 2010;Riu et al, 2011). Tetrabromobisphenol A (TBBPA) and tetrachlorobisphenol A (TCBPA) are halogenated derivatives of BPA (HBPAs), which feature bromine or chorine substituents on the phenolic rings, are used as flame retardants (Hakk and Letcher, 2003;Chu et al, 2005;de Wit et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics of BPA have been attributed to the effects on steroid hormone receptors such as ER (Matsushima et al, 2010). Okada et al (2008) reported that BPAF bound more strongly to ERa than BPA, and that it could cause adverse reproductive and developmental effects in several different in vivo and in vitro models (Akahori et al, 2008;Bermudez et al, 2010). TBBPA showed a weak estrogenic response in cultured MCF-7 breast cancer cells (Olsen et al, 2003), and inhibited in vitro estradiol sulfonation (Hamers et al, 2004), indicating the potential for both direct and indirect estrogenic activity in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…11,12,13,37) The binding affinity of BPAF was approximately 20 times stronger and 48 times stronger than that of BPA as a ligand for ERα and ERβ, respectively.…”
Section: )mentioning
confidence: 99%